2017
DOI: 10.1021/acs.cgd.7b00731
|View full text |Cite
|
Sign up to set email alerts
|

Process Intensification through Continuous Spherical Crystallization Using an Oscillatory Flow Baffled Crystallizer

Abstract: Drug substance purification by crystallization is a key interface in going from drug substance synthesis to final formulation and can often be a bottleneck in process efficiency. There has been increased importance in the development of continuous crystallization systems of active pharmaceutical ingredients to produce crystals with targeted physical and biopharmaceutical properties. Continuous spherical crystallization (CSC) is a process intensification technique that can address many of the present flaws (e.g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 32 publications
0
36
0
Order By: Relevance
“…The authors, therefore, implied that increased agglomerate collisions contribute to the agglomerate compaction process. Peña et al [59] found that a high concentration of solids did not yield efficient agglomeration, or operation, for their benzoic acid system using a continuous oscillatory flow baffled crystalliser; requiring operating conditions that significantly differed from previous benzoic acid studies in various systems to achieve spherical agglomeration [37,46,56].…”
Section: Effect Of the Initial Precipitated Particles On Agglomerationmentioning
confidence: 96%
“…The authors, therefore, implied that increased agglomerate collisions contribute to the agglomerate compaction process. Peña et al [59] found that a high concentration of solids did not yield efficient agglomeration, or operation, for their benzoic acid system using a continuous oscillatory flow baffled crystalliser; requiring operating conditions that significantly differed from previous benzoic acid studies in various systems to achieve spherical agglomeration [37,46,56].…”
Section: Effect Of the Initial Precipitated Particles On Agglomerationmentioning
confidence: 96%
“…However, these recom mendations are not always used in practice. For example, many continuous crystallization processes in oscillatory baffled reactors have been operated with velocity ratios near the upper limit of the recommended range, or even with higher values, to ensure solid suspension and uniform particle size and distribution (Briggs et al, 2015;Kacker et al, 2017;Peña et al, 2017;Siddique et al, 2015;Zhao et al, 2014). Indeed, whilst RTD mea surements are a good means to characterize mixing in COBRs for operations that require long residence times (e.g.…”
Section: Nomenclaturementioning
confidence: 99%
“…Some of the pain points around management of secondary nucleation issues that are inherent to agitated crystallizers need to be addressed. Impeller free crystallizers such as oscillatory baffled crystallizers 39,40 and fluidic oscillators 41 pose viable technology options and need concerted efforts for further development and consistent deployment.…”
Section: Enabling Technologies For Challenging Purificationsmentioning
confidence: 99%